PELAKSANAANEKSEKUSIPUTUSAN PENGADILANDALAMPERKARA PERDATA TERHADAP ASET BUMN - Charles Silalahi; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2015)
ABSTRACT State Owned Enterprises (SOE) is a business entity wholly or largely owned by the state capital through direct investments from sovereign wealth pengaturanya separated and regulated in Law No. 19 Year 2003 on SOEs and the Law No. 40 Year 2007 About the Company Limited. But there are many cases of failure by not executed a civil suit over the object of wealth owned by the Court was interpreting SOE’s property is state property that is subject to the law of the State Treasury. Regulation of Wealth Owned Enterprises as a form of wealth separated state regulated in Law Number 19 Year 2003 regarding SOEs and Law No. 40 of 2007 on Limited Liability Companies. Wealth Enterprises is the object Civil Lawsuit Case. When the state capital in the form of shares included in the Persero of wealth separated state, for the sake of intellectual property law becomes Persero. No longer the nation's wealth. This is based on Article 1 (1) and figure (2) jis Article 1 (10) and Article 4 paragraph (1) of state-owned enterprises, as well as Article 1 (1) in conjunction with Article 7, paragraph (7) letter a of Law PT also principles of law 'separate legal entity', wealth separated state and are included as capital assets Persero Persero. Consequently all the wealth obtained either through the inclusion of the country as well as those derived from business activities Persero, by law, a wealth Persero itself. Analysis of the Supreme Court delayed the execution of the provisions referring to Law. 1 of 2004 on State Treasury, Article 1 number 10, 11 and 50 then there is a conflict of laws (antinomie) the rule of law. This is an issue that the Supreme Court ruling execution can not be carried out above. To complete the 'antinomie' rule of law courts should use a